PENGEMBANGAN BUKU AJAR KIMIA KELAS XII SMA/MA SEMESTER II TERINTERNALISASI NILAI KARAKTER SESUAI DENGAN KURIKULUM 2013 - ikhwani ikhwani; Ikhsan Maulidi (Lantanida Journal, 2018)
The aim of this research was: (1) to give the standardization of BSNP information from a chemistry text book of the 2nd semester in class XII that internalized by character value in accordance with the curriculum development of 2013, (2) to see the result of learning and to know the result of students' attitude observation in the learning process. The benefits of this research was the existence of textbooks that fit into BSNP standard has been already good and adding the scientific information. The method used in this research was: Research and Development method by using BSNP Standardization in the chemistry book that validated by chemistry teacher in Langsa city and the application test in book development and doing observation process toward student attitude to learning. Based on the research that has been done, it is found that: (1) the development of textbooks has fulfilled the standard of content feasibility assessment with a score about 4.18, score language about 4.64, presentation of score about 4.6 and graphic book or score about 4.5, so it was valid. (2) the students learning outcomes by using this book book indicate the increasing of students' knowledge from the average score of pretest score of 43.3 to postes of 91.66. (3) The result of the attitude assessment was shown from the observation value to the student discussion attitude with the cooperation was score about 2.4, the curiosity score about 2.8, attitude score about 2.6 and communication score about 3.1. The conclusions of this research, were: (1) the result of the book development has been very feasible to use, (2) the increasing of student learning outcomes equal to 84.78%. (3) There is a change in student character to be better.